تحليل تباين طرق الري بالمياه المالحة على انتاجية محصول البطاطا في منطقة الوادي بالجزائر 20: ANALYSIS OF VARIATION SALINE WATER IRRIGATION METHODS ON PRODUCTIVITY POTATO CROP IN EL-OUED REGION ،ALGERIA 2019 - أمين بن سعيد; مسعودي محمد; نذير غنية (Journal of North African Economies, 2025)
This paper-targeted study significant of the difference in the irrigation method of the potato crop in El-oued region in explaining the severity of the crop productivity being affected by water salinity based on initial data for a random sample of 97 products during the fall season of 2019. As a standard, the paper used a multiple logarithmic regression model, and applied least squares (OLS) method to estimate its parameters. According to the results of the model, the study concluded that the negative effect of water salinity has a statistical significance in both irrigation methods. From the equation of the relationship it appears that the higher the salinity of irrigation water by 1%, the potato yield decreased by 2.49% in the areas irrigated by drilling and by 9.94% in the areas irrigated by sprinkler. With a statistically significant difference of 7.45% in favor of the drilling irrigation method. Accordingly, the study recommended the necessity of adopting the drilling irrigation method to overcome the severity of the effect of salinity of irrigation water on crop productivity and achieve significant economic benefits in this branch.